2020
DOI: 10.3758/s13414-020-02179-9
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory action effects facilitate the performance of motor sequences

Abstract: Research has shown that contingent, distinct action effects have a beneficial influence on motor sequence performance. Previous studies showed the beneficial influence of task-irrelevant action effects from one modality (auditory) on motor sequence performance, compared with no task-irrelevant action effects. The present study investigated the influence of task-irrelevant action effects on motor sequence performance from a multiple-modality perspective. We compared motor sequence performances of participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The posture control has the purpose of orienting and balancing the body for the activities' satisfactory performance, utilizing the sensorial systems involved in the balance: vestibular, somatosensory, and visual, with the main source of information being visual in the beginning of the child's motor development a [6,7]. The postural balance is the relative balance of the internal and external forces, which acts on the body during motor actions, and, at the same time, the execution of these motor actions influences the obtainment of sensory information [8]. Based on this information, the postural control identifies the operation of the associated body segments and their strength to control the adequate and appropriate muscular activity for this activity, maintaining the balance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The posture control has the purpose of orienting and balancing the body for the activities' satisfactory performance, utilizing the sensorial systems involved in the balance: vestibular, somatosensory, and visual, with the main source of information being visual in the beginning of the child's motor development a [6,7]. The postural balance is the relative balance of the internal and external forces, which acts on the body during motor actions, and, at the same time, the execution of these motor actions influences the obtainment of sensory information [8]. Based on this information, the postural control identifies the operation of the associated body segments and their strength to control the adequate and appropriate muscular activity for this activity, maintaining the balance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Congruent multimodal stimuli such as audiovisual information was found to promote faster and more accurate responses than receiving audial or visual stimuli ( Van Wanrooij et al, 2009 ; Tang et al, 2016 ). Luan et al (2021) explained that faster motor sequence responses were due to the enhanced contiguous action effects ( Luan et al, 2021 ). Other studies suggested that the response augmentation was due to a super-additive effect occurred when congruent multimodal stimuli are processed ( Ren et al, 2017 ; Zou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%